L'ouverture de l'Arctique : enjeux géoéconomiques et enjeux de puissance de la Fédération de Russie - Ruaut, Hélène (HAL CCSD, 2016)
In the 2050’s, the Arctic Ocean will probably be ice-free in summer. Thus, huge hydrocarbon fields will technically be exploitable. The Russian Federation has sovereign rights on 40% of the Arctic territory. It particularly makes it a key actor in the region. Today, Russia claims a maritime area around one third of all the Arctic Ocean. Moscow currently plans to develop a new shipping route lengthwise its Siberian coasts, and to exploit the offshore oil and gas resources. Therefore, Russia could surge its hydrocarbons production and exports. It will be a way not only to stand as a leader in the Arctic, but also a way to enhance its visibility and its influence on the international stage. This short thesis analyzes the Arctic subsoil wealth, in contrast to the extreme constraints of such territories located beyond the Arctic Circle. It studies also Moscow’s prospects for offshore oil and gas mining. Could Russia regain its status of powerful state through the development and the exploitation of the Arctic region? À l’horizon 2050, l’océan Arctique, libre de glace durant tout l’été, rendra techniquement exploitables d’immenses gisements d’hydrocarbures. La Fédération de Russie, souveraine sur environ 40 % du territoire arctique, est un acteur clé dans la région. Aujourd’hui, elle y revendique un espace maritime représentant près du tiers de la surface de l’océan. Moscou envisage ainsi d’ouvrir une nouvelle voie maritime le long de ses côtes sibériennes, et de développer l’exploitation du gaz et du pétrole offshore de la région. Cela lui permettrait d’augmenter considérablement sa production et ses exportations d’hydrocarbures. Ce serait alors un moyen pour l’État russe de s’affirmer comme leader du monde arctique, et ainsi d’accroître sa visibilité et son influence sur la scène internationale. Ce mémoire étudie la richesse du sous-sol arctique, conditionnée par les contraintes extrêmes des territoires situés au-delà du Cercle Polaire, et analyse également la perspective d’extraction offshore qu’ambitionne ...